Applying the regularized derivatives approach in Euler deconvolution and modeling geophysical data to estimate the deep active structures for the northern Red Sea Rift region, Egypt - SALEH, Salah; PAŠTEKA, Roman (Contributions to Geophysics and Geodesy, 2012)
The Red Sea is considered to be a typical example of a newly formed ocean. Moreover the northern Red Sea region and Gulf of Suez are generally important due to their hydrocarbon resources. Estimation of higher derivatives of potential fields represents a significant role in geophysical interpretation (qualitative and/or quantitative), as has been demonstrated in many approaches. One of the most popular methods, employing higher derivatives is the well known Euler deconvolution method. In this method it is very important to stabilize the derivatives evaluation, because they are very sensitive to noise and errors in the interpreted field. One way to stabilize higher derivative evaluation is the utilization of the Tikhonov regularization. We show the influence of regularized derivatives on the properties of the classical 3D Euler deconvolution algorithm and apply it to geophysical potential field data from the Red Sea Rift and its surroundings. The solution obtained with regularized derivatives gives better focused depth-estimates, which are closer to the real position of sources; the results presented here can be used to constrain depth to active crustal structures (boundaries and volcanisms) for northern Red Sea rift. Estimated Euler solution map from Bouguer data utilizing the Tikhonov regularization reveals both the continental-oceanic crust boundary and several shallow listric normal faults spreading on the Red Sea margins having NW–SE direction, suggesting NE–SW extension in these regions. Also, generalized depth model for the structure of the Gulf of Aqaba (three pull-apart basins) was well recognized from this map. However, Euler solutions with band pass filter of magnetic data gives best depth-estimates connected with the volcanic intrusive bodies (intense magmatic activity) prevalent on and around the axial trough transform faults resulted from initiation of Red Sea Rift. This depth estimation was derived resulting different structural indexes (SI).